Investigating contributions to elevated surface ozone in the Colorado Front Range during summer 2015 - Lindaas, Jakob, author; Fischer, Emily V., advisor; Farmer, Delphine K., committee member; Ravishankara, A. R., committee member (Colorado State University. Libraries, 2018)
Tropospheric ozone (O3) is a significant pollutant in the Colorado Front Range. The northern Front Range metropolitan area (NFRMA) has exceeded the U.S. EPA national ambient air quality standard for O3 since 2008. While many regions in the country have experienced downward trends in ground-level O3, the NFRMA O3 mixing ratios have remained stagnant despite efforts to reduce precursor emissions. Rapid population growth and a boom in oil and natural gas development over the past 15 years have changed the quantity and spatial distributions of many important O3 precursors. O3 precursors may also be transported into the NFRMA, such as during wildfire smoke events. Here I use in situ measurements of O3, a suite of volatile organic compounds (VOCs), and reactive oxidized nitrogen species collected during summer 2015 at the Boulder Atmospheric Observatory (BAO) in Erie, CO, to investigate the contribution of different VOC sources to elevated surface O3 in the NFRMA. The first analysis combines observations of acyl peroxy nitrates (APN) and a previously described positive matrix factorization of the VOCs to investigate the contribution of different VOC sources to high O3 abundances at BAO. Based on the ratio of PPN to PAN, I find that anthropogenic VOC precursors dominate APN production when O3 is most elevated. Propane and higher alkanes, primarily from oil and natural gas emissions in the Colorado Front Range, drive elevated PPN to PAN ratios during high O3 events. The percentage of OH reactivity associated with oil and gas emissions is also positively correlated with O3 and PPN/PAN. Lastly, idealized box model simulations are used to probe the chemical mechanisms for these observations. I find that VOC precursor mixtures dominated by oil and gas emissions create abundant and more efficient peroxy radical intermediates compared to mixtures dominated by traffic or biogenic emissions. This work may help guide efforts to control O3 precursors in the NFRMA. The second analysis examines the impact of wildfire smoke on O3 abundances via a case study. Aged wildfire smoke impacted BAO during two distinct time periods during summer 2015: 6 – 10 July and 16 – 30 August. The smoke was transported from the Pacific Northwest and Canada across much of the continental U.S. Carbon monoxide and particulate matter increased during the smoke-impacted periods, along with acyl peroxy nitrates and several VOCs that have atmospheric lifetimes longer than the transport timescale of the smoke. During the August smoke-impacted period, nitrogen dioxide was also elevated during the morning and evening compared to the smoke-free periods. There were nine empirically defined high O3 days during our study period at BAO, and two of these days were smoke-impacted. I examined the relationship between O3 and temperature at BAO and found that for a given temperature, O3 mixing ratios were greater (~10 ppbv) during the smoke-impacted periods. Enhancements in O3 during the August smoke-impacted period were also observed at two long-term monitoring sites in Colorado: Rocky Mountain National Park and the Arapahoe National Wildlife Refuge near Walden, CO. Given that the relative importance of wildfire smoke for air quality over the western U.S. is expected to increase as the climate warms and anthropogenic emissions decline, this case study offers important insights into how aged wildfire smoke can influence atmospheric composition at an urban site.
Keywords: Colorado; VOCs; acyl peroxy nitrate; wildfire smoke; ozone